Efektivitas Penerapan Model Pembelajaran Missouri Mathematics Project dengan Metode Two Stay Two Stray terhadap Kemampuan Pemecahan Masalah Matematika Peserta Didik - Naharullah, Ahmad Sazky; Rasyid, Muhammad Rusydi; Baharuddin; Suharti; A. Sriyanti (Al Asma: Journal of Islamic Education, 2023)
This research aims to determine the effectiveness of using the Missouri Mathematics Project learning model with the Two Stay Two Stray method on students' mathematical problem-solving abilities. This research is a quasi-experiment with a research design, namely Quasi Experiment Design. The research population involved all class VII students at MTs Madani Alauddin. The research sample was class VII A as the experimental class and VII B as the control class, selected using a simple random sampling technique. The instrument used is a test instrument in the form of a description test. Descriptive and inferential statistical analysis are the methods used for data analysis. This research showed that using the Missouri Mathematics Project learning model with the Two Stay Two Stray method effectively improved the mathematical problem-solving abilities of class VII students at MTs Madani Alauddin Pao-Pao.